MODAL VERBS USED IN PERMISSION, OFFER, OBLIGATION, AND POSSIBILITY - Komang Astiari; Dewa Made Agustawan; Made Detrichyeni Winaya (Universitas Warmadewa, 2024)
This study investigated how modal verbs are used by 4 level of students taking IELTS preparation course in expressing permission, offer, obligation, and possibility. The objectives of the study were to analyze two major issues; 1. is there any significant different between male and female students in using modal verbs properly? and 2. is there any significant different in using modal verbs in regards to the level of the students? As the objectives of the research, 50 male and female students were chosen as a sample who later did a test comprising 40 statements of modal verbs as permission, offer, possibility, and obligation. As a result, the difference attitude between males and females in using modal verbs is significant. In addition, the result of this study revealed that the highest proportion of correct answers made was by advanced, upper intermediate, intermediate, pre-intermediate, and elementary, respectively.